The use of syntactic structures in written compositions as possible measures of language growth among students of the Basilan City High School - Alano, Angeles (Calsado) 1924- (s.n.], 1968)
Using the formal themes of the students of the Basilan City High School during the school year 1967-1968, the study sought to determine whether the syntactic structures used in written compositions can be used as valid and workable measures for language growth in English.